The use of modern computer technology to determine the possibility of acclimatization of adventitious phytophages in Ukraine during the analysis of phytosanitary risk (РRA) - BorzykhА.; Klechkovsky, Yu.; Titova, L.; Palagina, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The article contains information on the use of modern computer technologies to determine the possibility of acclimatization of adventitious phytophages in Ukraine during the analysis of phytosanitary risk. The use of modern computer programs Agro Atlas, MapInfo v.11.0 and Idrisi Taiga allowed in a short time to analyze the availability of fodder base (host plants) and the correspondence of ecoclimatic conditions of Ukraine, as AРR region, to the corresponding indicators of the modern range of pests and to identify potential acclimatization zones for Oemona hirta (lemon tree borer) and Thaumatotibia leucotreta (false apple moth).